2015
DOI: 10.14689/ejer.2015.61.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Developed Differentiation Approach on the Achievements of the Students

Abstract: Problem Statement: The present study is of importance for designing a differentiation approach, which enables gifted students to use their present potential in mathematics effectively and enables them to develop their achievement, while looking at the effect of the approach on both gifted and non-gifted students. Within the scope of the developed differentiation approach concerning mathematics education of gifted students, the present study is one of the limited studies with such a focus, which is why it is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 16 publications
0
19
0
1
Order By: Relevance
“…Papers reporting on the same project and outcomes were taken together as one study. The papers by Altintas and Özdemir (2015a,b) report on the same project. The same applies to two other papers as well (Vogt and Rogalla, 2009; Bruhwiler and Blatchford, 2011).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Papers reporting on the same project and outcomes were taken together as one study. The papers by Altintas and Özdemir (2015a,b) report on the same project. The same applies to two other papers as well (Vogt and Rogalla, 2009; Bruhwiler and Blatchford, 2011).…”
Section: Resultsmentioning
confidence: 94%
“…In Table 2, the characteristics and individual effects of the studies included in our review are summarized. The selection of studies includes eight quasi-experimental studies in which classes were randomly allocated to a control or experimental condition (Mastropieri et al, 2006; Richards and Omdal, 2007; Huber et al, 2009; Vogt and Rogalla, 2009; Little et al, 2014; Altintas and Özdemir, 2015a,b; Bal, 2016; Bhagat et al, 2016), three studies in which schools were randomly allocated to conditions (Wambugu and Changeiywo, 2008; Mitee and Obaitan, 2015; Bikić et al, 2016), and one survey-study (Smit and Humpert, 2012). These studies covered a wide range of academic subjects, including science, mathematics and reading.…”
Section: Resultsmentioning
confidence: 99%
“…Although various studies have focused on the effects of various grouping arrangements on the achievement of identified gifted students (e.g., Delcourt, Cornell, & Goldberg, 2007;Kim, 2016;van der Meulen et al, 2014;VanTassel-Baska, Zuo, Avery, & Little, 2002), it is important to also study the effects of the curriculum on gifted student achievement because of its salient influence on the development of gifted potential (Altintas & Ozdemir, 2015;Callahan, Moon, Oh, Azano, & Hailey, 2015;Gallagher, 2015;Jarvis, 2009).…”
Section: Curriculummentioning
confidence: 99%
“…Although students identified as gifted have a certain amount of potential, if they are not challenged in the classroom, their potential may atrophy (Altintas & Ozdemir, 2015). For example, without the opportunity to engage in tasks within their zone of proximal development, identified gifted learners may lose confidence in their ability to succeed on such tasks when presented (van der Meulen et al, 2014), possibly leading them to adopt an entity view of intelligence (Ablard & Mills, 1995).…”
Section: Challengementioning
confidence: 99%
“…Research has shown that student outcomes improve when the learning environment, content, process, and product is differentiated. Technology is a tool that can help meet these ends (Altıntaş & Ozdemir, 2015). The UDL principle of multiple means of representation is an important feature of the framework (Katz, 2015).…”
Section: Technologymentioning
confidence: 99%